PERANAN GURU DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA DINI MELALUI METODE EKSPERIMEN DI PAUD ASUHAN BUNDA KABUPATEN ASAHAN - Mhd.Habibu Rahman (QURROTI, 2019)
This paper presents the role of an educator in developing early childhood creativity through experimental methods. An educator must be able to provide active stimulation in exploring every child's creative potential. This study aims to determine the role of teachers in developing early childhood creativity and the types of experimental activities that can trigger early childhood creativity. Sources of data in this study include school principals, class teachers, and children. Data collection is done by observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Based on the results of research at Asuhan Bunda PAUD, it can be concluded that an educator has a fundamental role in every early childhood development, including children's creativity, an educator must provide active stimulation and explore all the potential for children's creativity, types of experimental activities carried out at Asuhan Bunda PAUD These include magic food, mix colors, and drink new flavors.